Adiponectin : a novel circulating anti-thrombotic factor in humans? - Yousaf, Tanzeel Ahmed (2011)
Adiponectin is an adipocyte-derived pro-inflammatory adipokine that regulates metabolic homeostasis, although it has been reported to modulate platelet function and thrombosis. In this study the effects of globular adiponectin (gAd), a novel platelet agonist that stimulates platelet aggregation was characterised. While it had been previously noted that gAd stimulated platelet aggregation through a tyrosine kinase-dependent mechanism, in this thesis we further elaborated the mechanisms underlying gAd-induced platelet aggregation by investigating the role of platelet secondary mediators, granule secretion and intracellular signalling events using a series of receptor antagonists and inhibitors. The experimental data demonstrated that gAd-stimulated aggregation required adenosine diphosphate (ADP) and thromboxane A2 (TxA2) to achieve the maximal response. Consistent with this, threshold concentrations of gAd could synergise with ADP. However, using receptor antagonists this synergy was found to occur via the Gi-coupled P2Y12 receptor and not Gq-coupled P2Y1. Since the secretion of ADP from platelet dense-granules is driven by protein kinase C (PKC), we examined the role of PKC in gAd-mediated platelet aggregation. Ablation of PKC using a general inhibitor reduced platelet aggregation and abolished dense-granule secretion stimulated by gAd. Importantly, the aggregation response and dense-granule secretion under conditions of PKC inhibition could be partially restored by ADP acting through the P2Y12 coupled Gi receptor and by adrenaline acting through the Gz-linked α2A adrenoceptor. Further examination of this pathway revealed that the activation of phosphatidyl-inositol-3-kinase (PI3K) was required to restore secretion. To clarify the role of PI3K in this process we measured Akt phosphorylation as a marker of PI3K activity. We found that ADP and adrenaline potentiated gAd-induced Akt phosphorylation which could be inhibited with a selective PI3Kβ isoform inhibitor and to a lesser degree α isoform inhibitor. These data demonstrate that gAd requires the release of platelet secondary mediators to induce full platelet aggregation and the potentiation of initialaggregation occurs through G-protein coupled receptors linked to Gi-coupled G-proteins. Furthermore, the stimulation of Gi/Gz coupled G-proteins can potentiate platelet aggregation by stimulating secretion through a PKC-independent manner. Since adiponectin accumulates at sites of vascular lesions, the ability of immobilised gAd to support platelet adhesion was examined. GAd supported the adhesion of platelets under static and flow conditions. Adhesion under static conditions was inhibited by the glycoprotein VI (GPVI) blocking antibody, 10B12, but not ethylene glycol-bis (β-aminoethyl ether)-N,N,N’,N’,-tetraacetic acid (EGTA), suggesting a GPVI-dependent and integrin-independent mechanism. Together these data significantly improve our understanding of the mechanisms by which gAd may promote unwanted platelet aggregation and adhesion at sites of vascular injury.
HydraID: hull:5447 Hydra Discover Access Group: public ETD Collection: ETDHullYorkMedicalSchool
Keywords: Medicine